Le tabellionage et l’histoire économique : l’exemple de la draperie rouennaise au Moyen Âge (1360-1415) - Jean-Louis Roch (Tabularia)
The study of tabellionage records can reveal the economic and social organisation of medieval industries, such as cloth production in late medieval Rouen. The earliest registers from Rouen, dating from 1360 onwards, preserve acts relating to commerce, but we do not always know the people behind the recorded names, and names are rarely accompanied by professions. Furthermore, from 1415 onwards, commercial matters relating to what is called “meuble” in Middle French disappear from the records. Any investigation is therefore restricted to a narrow period (1360-1415), and professions must be sought by examining craft regulations. Three series of acts reveal the various stages of cloth production: the purchase of the wool, the costs of dyeing, and the rental of facilities for stretching the cloth before sale, the “pentheurs” (large wooden poles), at the beginning and end of the process. According to the Florentine model, the medieval cloth trade was usually dominated by merchant-drapers who bought the wool, organised its manufacture into cloth and sold the finished product. It is unclear, however, whether this model works north of the Alps, and the present study instead reveals a world of small businesses that left little room for great merchant-capitalists. The investigation also reveals the importance of financial and family networks and the roles of mutual aid and a culture of trust. Alongside merchant-entrepreneurs, there were also small artisan-entrepreneurs.